Cardiac autonomic activity during daytime nap in young adults. (4th May 2017) - Cellini, Nicola; Torre, Jacopo; Stegagno, Luciano; Sarlo, Michela
Summary: The current study investigated both sympathetic and vagal autonomic patterns during a daytime sleep in 25 healthy adults (23.2 ± 2.4 years). Pre‐ejection period (PEP; related inversely to beta‐adrenergic sympathetic activity), the interval between consecutive R‐waves (RR) and frequency‐domain heart rate variability (HRV) were computed during pre‐nap wakefulness and undisturbed sleep stages. Results showed sleep‐related changes in RR and HRV measures, whereas PEP decreased significantly from pre‐nap to sleep, showing no differences across sleep stages. Moreover, pre‐nap PEP and HFnu (the normalized unit of the high‐frequency component of HRV) were associated negatively with sleep latency and wake after sleep onset. These results indicate a marked autonomic output reduction during daytime sleep, with different stage‐dependent fluctuations for sympathetic and vagal activity. Importantly, pre‐nap autonomic activity seems to modulate subsequent sleep quality.